Single‐ and Double‐Sided Chemical Functionalization of Bilayer Graphene. Issue 4 (20th November 2012) - Felten, Alexandre; Flavel, Benjamin S.; Britnell, Liam; Eckmann, Axel; Louette, Pierre; Pireaux, Jean‐Jacques; Hirtz, Michael; Krupke, Ralph; Casiraghi, Cinzia
Abstract An experimental study on the interaction between the top and bottom layer of a chemically functionalized graphene bilayer by mild oxygen plasma is reported. Structural, chemical, and electrical properties are monitored using Raman spectroscopy, transport measurements, conductive atomic force microscopy and X‐ray photoelectron spectroscopy. Single‐ and double‐sided chemical functionalization are found to give very different results: single‐sided modified bilayers show relatively high mobility (200–600 cm2 V−1 s−1 at room temperature) and a stable structure with a limited amount of defects, even after long plasma treatment (>60 s). This is attributed to preferential modification and limited coverage of the top layer during plasma exposure, while the bottom layer remains almost unperturbed. This could eventually lead to decoupling between top and bottom layers. Double‐sided chemical functionalization leads to a structure containing a high concentration of defects, very similar to graphene oxide. This opens the possibility to use plasma treatment not only for etching and patterning of graphene, but also to make heterostructures (through single‐sided modification of bilayers) for sensors and transistors and new graphene‐derivatives materials (through double‐sided modification).